Characterization and development of cassava (Manihot esculenta Crantz) / sugar palm (Arenga pinnata (Wurmb) Merr.) fiber- reinforced cassava starch hybrid composites - Edhirej, Ahmed Faraj Ibrahim Hissen (2017)
Cassava is a unique plant, which has a number of uses including the manufacture of various foods, bio-fibers, bio-composites and biopolymers. Moreover, it serves as a renewable energy source as a starch. A series of characterization experiments were carried out to explore the potential use of cassava starch, peel, bagasse, polymers, composites and hybrid composites. A casting technique was used to fabricate the specimens. The following five-phases process prepared the hybrid composites from cassava/sugar palm fibers and cassava starch. The first phase of the process studied the physical, morphological and thermal properties of cassava starch (CS), peel (CP) and bagasse (CB) obtained from a Malaysian cassava plant along with their chemical composition. Thermal characteristic studies using a Thermal Gravimetric Analyzer (TGA) and Differential Scanning Calorimetry (DSC) showed that cassava starch and fibers were thermally stable with a decomposition temperature of 172.87, 177.76 and 169.23 ºC for cassava starch, peel and bagasse, respectively. A study on morphological surface indicated that cassava starches were rounded and oval-shaped, bagasse polygonal shaped and peel exhibited as both round and polygonal. The carbohydrate content in starch was 86.47 g/100g. The study showed that the cassava peel and bagasse contained high concentrations of hemicellulose at 23.38, 29.26 %, respectively. It can be concluded that, cassava starch and fiber are suitable to develop materials with acceptable mechanical and thermal properties for various applications such as packaging, automotive and agro-industrial applications. Phase two involved an investigation of the effects of plasticizers (Fructose, Urea, Triethylene glycol and Triethanolamine), with different concentration, on the physical, thermal and mechanical properties of cassava starch-based films. The moisture content, water solubility and water absorption of the films increased with increasing plasticizer content. Fructose plasticized films showed excellent water resistance when compared to other plasticizers. Film plasticized with 30% fructose showed the highest density at 1.74 g/cm3, while the lowest water content at 10.96% and water absorption at 110%. Films containing fructose presented smooth surfaces without pores. The relative crystallinity decreased with increasing plasticizer content. The film plasticized by 30% fructose presented higher relative crystallinity (0.31). Film plasticized with 30% fructose showed the tensile strength (4.7 MPa) and tensile modulus (69 MPa). Thus, fructose was the most efficient plasticizer agent among the various plasticizers used in this study. Phase three focused on the use cassava peel with two different particle sizes as a natural filler for thermoplastic starch (TPS) based on the cassava starch. The addition of peel resulted in an increase in the thickness, water content and water absorption of the films while it decreased the density and water solubility. Moreover, scanning electron microscopy showed that the films containing smaller size of peel had a better compact structure and a homogeneous surface without pores. The addition of 6% peel increased the elastic modulus and tensile strength up to 449.74 and 9.62 MPa, respectively, this being the most efficient reinforcing agent. Also, the temperature variation of the dynamic-mechanical parameters of cassava starch/peel composites was investigated using a DMA test. It was observed that the incorporation of peel increased the tensile strength and modulus. In conclusion, cassava starch/peel composite films are suitable for various purposes such as packaging, automotive and agro-industrial application, at a lower cost. In phase four, cassava starch-based composite film was prepared using the fibrous residual from starch extraction (cassava bagasse) as a filler. Composite films were prepared through the casting technique using fructose as plasticizer and various size and concentration of bagasse. The size and concentration of bagasse significantly influenced the physical properties. It increased the thickness, water solubility and water absorption. It reduced the water content and density of the film. However, there was no significant effect on thermal properties with the addition of bagasse. XRD studies indicated an increase in the crystallinity of the composites with increasing fiber content. SEM micrographs indicated that films with a smaller size of bagasse showed better compact structure and a homogeneous surface. The modulus and tensile strength of composite films was increased from 69.03 to 581.68 MPa and from 4.7 to 10.78 MPa, respectively, by the addition of 6% bagasse, showed the most efficient reinforcing agent owing to its remarkable physical and mechanical properties. In the final phase, the hybrid composites were successfully prepared using different amounts of fibers, the hybrid composite contains (6% w/w dry starch) cassava bagasse and (0, 2, 4, 6 and 8 % w/w dry starch) sugar palm fiber. The specimens were prepared by a casting technique using fructose as plasticizer for the cassava starch. The incorporating of SPF significantly influenced the physical properties. It increased the thickness, while it decreased density, water content, water solubility and water absorption of the films. Moreover, XRD studies indicated increasing crystallinity of the composites with increasing of fiber content. The incorporation of SPF increased the relative crystallinity up to 47%, compared to 32% of the CS film. The water barrier vapor permeability (WVP) values decreased with increasing SPF content. The mechanical properties of the films improved with the incorporation of fibers. The modulus and tensile strength of the films increased from 69.03 to 1114.6 MPa and from 4.7 to 20.72 MPa, respectively for film contains 6% CB and 6% SPF, which was the most efficient reinforcing agent. Also, dynamic-mechanical properties of the hybrid composites were investigated using a DMA test. It was observed that the incorporation of SPF increased the storage modulus (E’) value from 0.457 GPa of CS to 1.490 GPa of CS-CB/SPF8 hybrid composite film. In conclusion, CB/SPF reinforced CS hybrid composite films are suitable for various purposes such as packaging, and agro-industrial applications, at a much lower cost while having sustainable environmental automotive benefit.